Pelaksanaan Hak Dan Kewajiban Terhadap Pekerja/Buruh Di Pt.Semen Indonesia Distributor Lombok Berdasarkan Undang-Undang Nomor 13 Tahun 2003 Dan Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Lalu Gilang Arnawa; H. Zaeni Asyhadie (Fakultas Hukum Universitas Mataram, 2022)
This study aims to determine how the rights and obligations of workers/laborers in PT. Semen Indonesia Distributor Lombok in terms of Law Number 13 of 2003 concerning Manpower and Law Number 11 of 2020 concerning Job Creation and to find out factors that hinder the implementation of the rights and obligations of workers/ laborers who work at PT. Semen Indonesia Distributor Lombok. This research is an empirical normative legal research. This study concludes that the implementation of workers' rights has been carried out well. However, there are also workers' rights that are still not maximized, namely the right to social security for non-permanent workers, and regarding occupational health and safety (K3), it is necessary to have stricter regulations and supervision. from related parties in order to achieve a balance between the rights and obligations of workers.